2017
DOI: 10.1111/aor.12967
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Valve Opening With Two Rotary Left Ventricular Assist Devices for Biventricular Support

Abstract: Right ventricular failure is a common complication associated with rotary left ventricular assist device (LVAD) support. Currently, there is no clinically approved long-term rotary right ventricular assist device (RVAD). Instead, clinicians have implanted a second rotary LVAD as RVAD in biventricular support. To prevent pulmonary hypertension, the RVAD must be operated by either reducing pump speed or banding the outflow graft. These modes differ in hydraulic performance, which may affect the pulmonary valve o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Eric L. Wu et al of The Prince Charles Hospital, Brisbane, Australia, reported on pulmonary valve opening (PVO) with two rotary left ventricular assist devices (LVAD) for biventricular support by comparing PVO with the right VAD operated at reduced speed or with a banded outflow graft. Baseline conditions were simulated in a mock circulation loop.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%
“…Eric L. Wu et al of The Prince Charles Hospital, Brisbane, Australia, reported on pulmonary valve opening (PVO) with two rotary left ventricular assist devices (LVAD) for biventricular support by comparing PVO with the right VAD operated at reduced speed or with a banded outflow graft. Baseline conditions were simulated in a mock circulation loop.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%
“…1 With the development of technologies, VADs have evolved from pulsatile volume displacement pumps (first generation) to rotary pumps (second and third generation). 2 To minimize mechanical wear, the third generation VADs are operated with hydrodynamic or magnetic levitation system to suspend the impellers in the pump housings. 2 However, impeller touchdown can happen in such systems due to pump start up, pump stoppage, ventricular suction, unbalanced force caused by change in patient and/or device state, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…2 To minimize mechanical wear, the third generation VADs are operated with hydrodynamic or magnetic levitation system to suspend the impellers in the pump housings. 2 However, impeller touchdown can happen in such systems due to pump start up, pump stoppage, ventricular suction, unbalanced force caused by change in patient and/or device state, and so forth. Due to the poor anti-wear properties of titanium (Ti) and its alloy Ti6Al4V (commonly used for VADs manufacturing), such contact can cause damage to the surface of the housing wall and impeller.…”
Section: Introductionmentioning
confidence: 99%
“…These rotary VADs use either mechanical bearings (in second-generation pumps) or hydrodynamic/magnetic levitation systems (in third-generation pumps) to suspend impellers within their pump housings. 3 As the key components of rotary VADs, impellers and housings have stringent requirements on wear resistance and hemocompatibility of their construction materials and surfaces. The interaction between blood and the blood-contacting surfaces of pumps like impellers and housing walls can cause complications like thrombosis and hemolysis.…”
mentioning
confidence: 99%
“…However, these devices were large and not fully implantable and had many moving parts that were prone to wear and other forms of mechanical damage that caused device failure. 3 The second and third generations of devices are developed as small (some are fully implantable) rotary pumps which generate continuous flow. These rotary VADs use either mechanical bearings (in second-generation pumps) or hydrodynamic/magnetic levitation systems (in third-generation pumps) to suspend impellers within their pump housings.…”
mentioning
confidence: 99%